Understanding Cosmological Measurements with a large number of mock galaxy catalogues. Issue Volume 10:Issue S306(2014) (1st July 2015) - Manera, M.; Percival, W. J.; Ross, Ashley; Tojeiro, R.; Samushia, L.; Howlett, C.; Vargas-Magaña, M.; Burden, A.; ,
Abstract: Mock galaxy catalogues are essential to the error analysis of cosmological measurements from big galaxy surveys covering thousands of square degrees in the sky, like BOSS, WiggleZ, DES, or Euclid. The PTHalos mock galaxy catalogues were used in the BOSS survey to analyse the BAO measurement from the CMASS ( z ∼ 0.57) and LOWZ ( z ∼ 0.32) galaxy samples, which provided the best estimate to date of the cosmic distance scale from galaxy surveys at these redshifts. We review the PTHalos mocks galaxy catalogues and their key contributions to these analyses.